ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN KARIR MAHASISWA AKUNTANSI (Studi Empiris Mahasiswa Akuntansi di Perguruan Tinggi di Semarang ) - Rahmat Fajar Ramdani; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2014)
The purpose of this study is to investigate and analyze factors influencing accounting students in the career selection ( public accounting or non-public accounting) . Factors influencing the selection of career are financial rewards, profesional training, profesional recognation, social values, work environment, labor market consideration, personality and act of gender.The samples used in this research are 120 respondents. The samples are collected from UNDIP, UNNES, UNISULA, and UNIKA The hypothesis, were analized by logistic regression. The results show that financial reward, profesional training, profesional recognation, labor market consideration, and gender have significant effect on career selection to become public accountants or non-public accountants, however social values, work environment and personality variables do not have significant effect on career selection to become public accountants or non public accountants.